Pola Manajemen Pendidikan Karakter Siswa Dalam Meningkatkan Kedisiplinan Siswa SMKS Sayid Sabiq Indramayu - Lilis Suryani (LPPM Bunga Bangsa Cirebon, 2022)
This study discusses the Management Pattern of Student Character Education in Improving Student Discipline of Sayid Sabiq Indramayu Vocational School which is motivated by the character education program owned by the school to be applied to students. This study aims to determine the pattern of student character education management applied in improving the discipline of Sayid Sabiq Indramayu Vocational High School students. This research method uses qualitative research with a descriptive approach. The data collection uses observation, interviews, and documentation.Based on the results of research and discussion on the Pattern of Student Character Education Management in Improving Student Discipline at Sayid Sabiq Indramayu Vocational School, it can be concluded that 1. Management of Student Character Education at Sayid Sabiq Indramayu Vocational School is carried out by implementing character education that is able to develop student potential, as well as improve student character and morality. which is not good. Management of Student Character Education starts from the process of accepting new students until the student graduates so that the student character education program is successful, effectively, and efficiently. 2. Student discipline at Sayid Sabiq Indramayu Vocational School can be said to be good because students are able to carry out their obligations and leave prohibitions and can participate in every activity that has been determined by the school. 3. The Management Pattern of Student Character Education in improving student discipline at the Sayid Sabiq Indramayu Vocational School is carried out through good coordination with school principals, teachers, students, parents and school security officers to ensure that the programs set by the school can be implemented and followed by students. Abstrak Penelitian ini membahas tentang Pola Manajemen Pendidikan Karakter Siswa Dalam Meningkatkan Kedisiplinan Siswa SMKS Sayid Sabiq Indramayu yang dilatarbelakangi adanya program Pendidikan karakter yang dimiliki sekolah untuk diterapkan pada siswa. Penelitian ini bertujuan untuk mengetahui pola manajemen pendidikan karakter siswa yang diterapkan dalam meningkatkan kedisiplinan siswa SMKS Sayid Sabiq Indramayu. Metode penelitian ini menggunakan penelitian kualitatif dengan pendekatan deskriptif. Adapun pengumpulan datanya menggunakan observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian dan pembahasan tentang Pola Manajemen Pendidikan Karakter Siswa Dalam Meningkatkan Kedisiplinan Siswa SMKS Sayid Sabiq Indramayu dapat disimpulkan bahwa 1. Manajemen Pendidikan Karakter Siswa di SMKS Sayid Sabiq Indramayu dilakukan dengan menerapkan Pendidikan karakter yang mampu mengembangkan potensi siswa, serta memperbaiki karakter dan akhlaq Siswa yang kurang baik. Menejemen Pendidikan Karakter Siswa di mulai dari proses penerimaan siswa baru sampai dengan siswa tersebut lulus sehingga progam Pendidikan karakter siswa mendapatkan berhasil secara efektif, dan efisien. 2. Kedisiplinan Siswa di SMKS Sayid Sabiq Indramayu dapat dikatakan baik karena siswa mampu melaksanakan kewajiban dan meninggalkan larangan serta dapat mengikuti setiap kegiatan yang telah ditentukan oleh sekolah. 3. Pola Manajemen Pendidikan Karakter Siswa dalam meningkatkan kedisiplinan Siswa di SMKS Sayid Sabiq Indramayu dilakukan dengan jalur koordinasi baik kepada kepala sekolah, guru-guru, siswa, orang tua dan petugas keamanan ssekolah untuk menjamin program yang ditetapakan sekolah dapat dilaksanakan dan diikuti oleh siswa.